EFFICACY OF IBUPROFEN IN TREATMENT OF PAIN IN CHILDREN: SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED STUDIES - R.T. Saygitov ("Paediatrician" Publishers LLC, 2010)
The article presents results of systematic review of data on prophylactic and therapeutic efficacy of ibuprofen. Data search was performed by PubMed database and Google search. 27 publications for analysis were available. Prophylactic efficacy of ibuprofen was studied in 14 studies. Summarizing of the results showed that ibuprofen prevents pain and decreases its following intensity after different surgical or dental operations. There is no significant difference in prophylactic efficacy of single dose ibuprofen and acetaminophen. Therapeutic efficacy of ibuprofen was described in 13 studies. Administration of the drug for pain stopping in children is reasonable. The analgesic effect of ibuprofen compared to placebo was shown in all studies of patients with migraine and diseases of ENT-organs. 5 studies performed in last 5 years showed efficacy of ibuprofen in trauma patients, including children with non-complicated fractures of extremities.Key words: children, pain, ibuprofen, prophylaxis, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):52-62)